Morphological, Physiological, and Transcriptional Changes in Crocus sativus L. Under In Vitro Polyethylene Glycol-Induced Water Stress - Suman Gusain; Rohit Joshi (Biology)
Saffron (Crocus sativus L.), a perennial geophyte from the Iridaceae family, blooms in autumn and thrives in Mediterranean-like climates. It is highly valued for its therapeutic and commercial uses. While saffron cultivation generally requires minimal water, insufficient irrigation can negatively impact its yield. Although numerous studies have explored the detrimental impact of drought on saffron under field conditions, its impact in vitro remains largely unexplored. The present study aims to investigate the effects of polyethylene glycol (PEG) 6000 at concentrations of 0%, 5%, and 10% in inducing drought stress on saffron shoots under controlled conditions. The research focuses on evaluating morphological, physiological, and biochemical changes and analyzing the expression of drought-responsive genes. Shoot establishment was carried out on Murashige and Skoog (MS) medium supplemented with 6 mg/L 6-benzyladenine (BAP) and 1 mg/L naphthaleneacetic acid (NAA), while PEG 6000 was used to induce drought stress. Various morphological, biochemical, and molecular parameters were assessed 30 days after stress induction. Increasing PEG concentrations in the medium significantly reduced shoot regeneration, leading to increased apical tissue browning. Significant chlorophyll and carotenoid level changes were observed in shoots exposed to higher PEG concentrations. PEG-induced drought led to decreased plant growth and biomass and lowered relative water content of leaves. Lipid peroxidation, membrane damage, and H2O2 content increased, indicating heightened stress levels. Proline concentration significantly increased in plants subjected to 5% and 10% PEG compared to controls. Non-enzymatic antioxidant activity (phenolics, flavonoids, % inhibition, total reducing power, and total antioxidant activity) also increased with the severity of stress. In contrast, a decrease in the activity of superoxide dismutase (SOD) and peroxidase was observed in PEG-treated shoots. Significant changes in the expression of drought-related genes, such as DREB1, DREB2, AREB1, DHN1 (Dehydrin), and SnRK2, were observed in shoots exposed to 5% and 10% PEG. In conclusion, the study highlights that PEG, as an inducer of drought stress, negatively impacts saffron’s growth and physiological responses under in vitro conditions. It also triggers significant changes in biochemical and molecular mechanisms, indicating the plant’s susceptibility to water scarcity.